Emisión de contaminantes atmosféricos del servicio de transporte colectivo de la carretera Iquitos-Nauta, Loreto 2023 - Navarro Tarazona, Grecia Greysi (2024)
The present work consists of the estimation of atmospheric pollutants emitted annually from the exhaust pipe of vehicle units of the Iquitos – Nauta 2023 collective transport service, such as carbon monoxide (CO), volatile organic compounds other than methane (NMVOC), nitrogen oxides (NOX), nitrous oxide (N2O), ammonia (NH3) and particulate matter (PM2.5). For this estimate, a mathematical model established by the 2019 air pollutant emissions inventory guide of the European Environmental Agency (EEA) was used, which is based on the distance traveled, number of vehicles and an emission factor for each pollutant. For this reason, a survey was carried out on a representative sample of 80 vehicle units, whose sample was made up of a quantity proportional to the total number of each vehicle agency in the population. The emission of atmospheric pollutants from each vehicle unit of the different transportation agencies was estimated based on the data collected, to subsequently obtain an average emission of pollutants by each agency, with the purpose of projecting the annual estimate of all the vehicles dedicated to this activity. The results of the estimation of atmospheric pollutants of the Iquitos – Nauta public transport service in 2023 reached values of 1,567,399.0 g/km CO, 924,767.6 g/km NMVOC, 554,365.2 g/km NOx, 105,893.1 g/km N2O, 26 142.3 g/km NH3, and 8 642.3 g/ km PM2.5.